The future for Eurozone financial stability policy - Karl Whelan (University College Dublin, UCD School of Economics, 2010)
The past few months have exposed serious problems in relation to Europe's ability to cope with financial stress. Placing the new Financial Stability funds on a permanent basis, in the form of a new European Monetary Fund will be required if Europe is to deal effectively with the serious debt problems of some Eurozone countries. However, this fund should exist to manage sovereign defaults in an orderly manner, not to prevent them altogether. Bank supervisors also need to publish regular stress tests, change their regulations on the risk weighting of sovereign debt and put new resolution procedures in place. Together, these reforms will allow Europe to deal with future sovereign debt problems without provoking a crisis.
hdl:10197/2660
Keywords: 330